Mineralogical and Chemical Characteristics of Marble of Bela Pola deposite (Geologica Macedonica, 2013)
This paper presents mineralogical characteristics of marbles from the Bela Pola deposit. We have made mineralogical-chemical analyses of marbles and associated minerals in them. The investigation was carried out at the Faculty of natural and technical sciences – Štip. Marbles from Bela Pola are dolomite and dolomite-calcite types. Microscope investigations have shown that marbles from Bela Pola have granoblastic structure but at some places it can be found with porphyroblastic structures. Percentage on calcite and dolomite is: 94.08% dolomite, 6.25% is calcite in white marbles. On the other hand calcite is present with 93% in gray marbles. Except dolomite and calcite also appear the following accessoring minerals: quartz, fluorite, corundum and paragonite. In general, after summarizing all the facts, which have resulted from this research we could say that, the Bela Pola marbles are massive, compact and white with high quality. In accordance to all formerly mentioned features, this marbles can be classified in the commercial group of marbles suitable for external application or internal design.